The Epidemiological and Clinical Aspects of Nasal Polyps that Require Surgery - Meymane Jahromi, Ahmad (Mashhad University of Medical Sciences, 2012)
INTRODUCTION: The objective of this retrospective cross-sectional study was to obtain epidemiological data from the charts of 297 patients with nasal polyposis who were operated on in a referral hospital in Mashhad and to determine the frequency of the presenting symptoms of nasal polyps. MATERIALS AND METHODS: The variables recorded included age, gender, the presence of asthma or allergic rhinitis, family history, and previous treatments. We studied the main symptoms of nasal polyposis (nasal obstruction, rhinorrhea, anosmia, headache, epistaxis, snoring, and so on), as well as ear problems and facial deformity. RESULTS: Nasal polyposis affects men (60.3%) more frequently, at a mean age of 39.5 years. The most frequent symptom was nasal blockage (81.1 %) followed by rhinorrhea (37.7%). A total of 11.1% of the patients had a history of epistaxis. Asthma was found in 10.4% of patients with nasal polyposis and the ears were affected in 5.1% of patients. In all, 7.4% of patients had first-degree relatives who suffered from asthma or allergic rhinitis. CONCLUSION: This study highlights the need for large-scale epidemiologic research exploring the prevalence and incidence of nasal polyposis in Iran.